PHENOTYPIC AND GENOTYPIC CHARACTERIZATION OF MULTIDRUG-RESISTANT KLEBSIELLA PNEUMONIAE PRODUCING EXTENDED-SPECTRUM Β-LACTAMASE AND CARBAPENEMASE - ROHIT KUMAR; RUMANA FAROOQ MIR; ROSY BALA; NARINDER KAUR; DIPANKAR BISWAS (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Antimicrobial resistance poses a worldwide health challenge with significant social and economic consequences. The increasing prevalence of extended-spectrum β-lactamases (ESBL) and carbapenemase (CP)-producing Klebsiella pneumoniae calls for urgent research and new drug development. These genes undermine infection control efforts because of their association with multidrug resistance (MDR). Methods: This cross-sectional study was conducted from April 2022 to April 2025 at the microbiology department of MMIMSR, Mullana, Ambala. Identification and antibiotic susceptibility testing for K. pneumoniae were performed using the Vitek-2 Compact (BioMérieux). The presence of ESBL and CP-producing isolates was phenotypically confirmed using the combined disc method. Genes KPC, NDM, IMP, VIM, OXA-48, TEM, CTX-M, and SHV were detected using singleplex conventional polymerase chain reaction. Results: Out of 612 K. pneumoniae isolates, 375 non-repetitive MDR strains were obtained from patients at M.M. Hospital, Ambala. The majority of these isolates came from males (57.6%), urine samples (61.3%), and hospitalized patients (75.5%). All isolates demonstrated complete resistance (100%) to β-lactams (Cephalosporins and carbapenems), with high resistance rates shown by cefepime (96.8%), ciprofloxacin (95.2%), gentamicin (93.6%), and trimethoprim-sulfamethoxazole (76%). Tigecycline (62%) and nitrofurantoin (53%) showed the most activity. ESBL production was identified in 51.2% of isolates, and CP production in 48.3%; Modified carbapenem inactivation method positivity was 70.1%, with 42.1% metallo- β-lactamase and 10.6% serine CPs. Among resistance genes, CTX-M (45.8%) and TEM (23.7%) were the most common ESBL determinants, while NDM (48.2%) and OXA-48 (37.8%) were the most prevalent CPs, followed by KPC (13.6%). The co-occurrence of genes was frequent, notably NDM+OXA-48 (16.2%) and triple KPC+NDM+OXA-48 (0.8%). All isolates were negative for SHV, IMP, and VIM genes. Conclusion: The findings highlight the need for urgent infection control. Policymakers should establish guidelines for regulating antibiotic sales and require susceptibility testing before prescribing antibiotics. Nationwide monitoring of carbapenem resistance and gene profiling is essential for better antimicrobial use.